Under the weather: mechanisms underlying avian responses to precipitation - Silber, Katherine M. M. (Kansas State University, 2023)
The goal of this dissertation is to understand how and why bird populations respond to precipitation. Bird responses to precipitation have been reported from most biomes, but the nature of those responses and vital rates affected differ among studies, hindering mechanistic understanding of links between demography and the environment. I combined intensive field studies in the mid-continental grasslands of the USA with a meta-analysis of responses to precipitation globally to elucidate mechanisms underlying responses. I first synthesized published evidence to test if life history traits or habitat characteristics mediate relationships between precipitation and reproductive success. Birds living at high elevations or having young requiring substantial parental care respond more negatively to precipitation than birds with other distributions or life histories, implicating both life history traits and habitat characteristics in mediating avian responses to precipitation. I then focused on a broader suite of vital rates in Grasshopper Sparrows, a grassland songbird in steep decline, that exhibits altricial development and experiences high variability in annual precipitation. Using a 10-year field-collected dataset of mark-resight and nesting data from the Konza Prairie in NE Kansas, I found that population growth rate was most sensitive to fluctuations in adult apparent survival (i.e. true survival and site fidelity) than other life stages. Under future precipitation regimes, my projections predict the population will likely be extirpated in the next 100 years. Given the importance of precipitation, survival, and movement in the dynamics of this population, I used mark-resight data of 1,332 territorial male Grasshopper Sparrows between 2013-2020 at the Konza Prairie to test the alternative drivers of inter-annual variability in survival and emigration. While survival was shaped by winter precipitation, emigration was shaped by 2-year lagged breeding season precipitation, and changes in the number of territorial males at a breeding site each year could be more strongly attributed to movement than mortality. Lagged responses suggested that relationships between precipitation and emigration are likely mediated by vegetation structure. Finally, I tested alternative explanations for the relationship between emigration and precipitation by determining the factors that drive settlement decisions. I paired mark-resight data from three grassland songbirds at the Konza Prairie with vegetation and topography data. Vegetation varied with land management and precipitation up to two years prior, consistent with links between precipitation and movement decisions. Birds selected territories on flat areas based on species-specific vegetation attributes, but all avoided woody vegetation cover. The simulated removal of isolated trees improved grassland songbird habitat by over 14 hectares. These results provide specific and achievable conservation recommendations with substantial impacts on declining grassland songbirds. At a local level, this dissertation provides a comprehensive explanation for how and why local variation in abundance of grassland bird occurs, and on a global scale, it helps explain why rain leads to divergent responses in species living in different regions and with different life histories.
Keywords: Precipitation; Population ecology; Birds; Dispersal; Habitat selection; Survival